2020
DOI: 10.3390/polym12081803
|View full text |Cite
|
Sign up to set email alerts
|

Thiolation of Biopolymers for Developing Drug Delivery Systems with Enhanced Mechanical and Mucoadhesive Properties: A Review

Abstract: Biopolymers are extensively used for developing drug delivery systems as they are easily available, economical, readily modified, nontoxic, biodegradable and biocompatible. Thiolation is a well reported approach for enhancing mucoadhesive and mechanical properties of polymers. In the present review article, for the modification of biopolymers different thiolation methods and evaluation/characterization techniques have been discussed in detail. Reported literature on thiolated biopolymers with enhanced mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 111 publications
0
35
0
Order By: Relevance
“…Highly effective technique such as thiolation has been attempted to improve the mucoadhesive property of polymers since tethered thiols have the capacity to form disulfide bridge with the cysteine residues in mucin [ 47 , 48 ]. However, the in vivo mucosal retention of thiolated polymer is short lived because the disulfide bonds formed between thiol groups and mucin are reversible.…”
Section: Design and Formulation Of Buccal Drug-delivery Systemsmentioning
confidence: 99%
“…Highly effective technique such as thiolation has been attempted to improve the mucoadhesive property of polymers since tethered thiols have the capacity to form disulfide bridge with the cysteine residues in mucin [ 47 , 48 ]. However, the in vivo mucosal retention of thiolated polymer is short lived because the disulfide bonds formed between thiol groups and mucin are reversible.…”
Section: Design and Formulation Of Buccal Drug-delivery Systemsmentioning
confidence: 99%
“…Different studies have reported that chelating [ 29 ], permeation [ 30 ] and, especially, mucoadhesive [ 31 , 32 ] properties can be improved when sulphur-containing molecules are attached to the alginate backbone. In particular, the synthesis of thiol-containing biopolymers offers numerous attractive features for a variety of biomedical applications in which the biomaterial can perform as a drug delivery system and bioadhesive [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymers have been proposed to be a safer alternative to conventional polymers in many biomedical applications such as tissue engineering scaffolds [9,10], drug delivery [11], biosensing [12], wound healing [13], obstetrics, and gynecology [14,15]. The invention pertains to developing new innovational biopolymer-based materials still challenging.…”
Section: Introductionmentioning
confidence: 99%